1992
DOI: 10.1152/jappl.1992.72.1.135
|View full text |Cite
|
Sign up to set email alerts
|

In vivo recording of electrical activity of canine tracheal smooth muscle

Abstract: Electrical activity of the tracheal smooth muscle was studied using extracellular bipolar electrodes in 37 decerebrate, paralyzed, and mechanically ventilated dogs. A spontaneous oscillatory potential that consisted of a slow sinusoidal wave of 0.57 +/- 0.13 (SD) Hz mean frequency but lacked a fast spike component was recorded from 15 dogs. Lung collapse accomplished by bilateral pneumothoraxes evoked or augmented the slow potentials that were associated with an increase in tracheal muscle contraction in 26 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…In normal subjects a consistent pattern of electrical activity was observed that was comparable to other smooth muscle organs, such as ureter, trachea or bowel [10][11][12]. During flaccidity, a high frequent basic activity with a low amplitude was found.…”
Section: Normal Subjectssupporting
confidence: 58%
See 2 more Smart Citations
“…In normal subjects a consistent pattern of electrical activity was observed that was comparable to other smooth muscle organs, such as ureter, trachea or bowel [10][11][12]. During flaccidity, a high frequent basic activity with a low amplitude was found.…”
Section: Normal Subjectssupporting
confidence: 58%
“…Also, the similarity of potentials recorded with needle electrodes and surface electrodes show that these recordings are of electrical and not of myogenic (movement) origin. Finally, cavernous smooth muscle electrical activity parallels elec trical activity recorded from other smooth muscle organs like ureter, trachea or stomach [10][11][12],…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Von den drei im menschlichen Körper vorkommenden Muskelarten (Herzmuskulatur, quergestreifte und glatte Muskulatur) wird die elektrische Aktivität der Herzmuskulatur mit dem Elektrokardiogramm (EKG) und die der Skelettmuskulatur mit dem Elektromyogramm (EMG) routinemäßig erfaßt. Elektromyographische Aufzeichnungen glattmuskulärer Zellen wurden unter experimentellen Bedingungen in den vergangenen 20 Jahren an verschiedenen Organsystemen durchgeführt: Ureter [4], Uterus [17], Kolon [11,20], Duodenum [1], Magen [10], Trachea [8], Gallenblase [9] und Gefäße [7]. Eine Messung der elektrischen Aktivität in der glatten Muskulatur hat sich bislang als klinisches Standardverfahren nicht durchsetzen können.…”
Section: Universität Magdeburgunclassified
“…In clinical routine, the electrical activity of cardiac muscle (ECG) and of striated muscle (EMG) has been registered for decades. Electrical activity of smooth-muscle organs such as ureter [1], uterus [2], colon [3,4], duodenum [5], gaster [6], trachea [7], gall bladder [8] and vessels [9] was registered mainly in a laboratory setting. This smoothmuscle EMG did not have a widespread clinical use since the above-mentioned organs needed surgical exposure Nevertheless, there were conflicting reports on normal and abnormal CC-EMG recordings due to a missing con sensus on the basic principles of the examination itself and the recording parameters.…”
Section: Introductionmentioning
confidence: 99%